HUBUNGAN KEMAMPUAN BERPIKIR LOGIS DAN KEMAMPUAN MATEMATIKA TERHADAP HASIL BELAJAR INFORMATIKA SISWA KELAS XI SMA AMAL MULIA BOARDING SCHOOL - Salsabila, Gina; Novalia, Melly; Benny Herlandy, Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between logical thinking ability and mathematical ability on Informatics learning outcomes of eleventh-grade students at SMA Amal Mulia Boarding School Pekanbaru. This research was motivated by variations in students' Informatics learning outcomes as well as differences in their logical thinking and mathematical abilities. The study employed a quantitative approach using an ex post facto correlational method. The sample consisted of 66 students selected through a saturated sampling technique. Data were collected through logical thinking tests, mathematics tests, and Informatics learning outcome tests. The data were then analyzed using normality, homogeneity, linearity, heteroscedasticity, and multicollinearity test, Pearson product correlation and multiple linear regression analysis. The results indicated that logical thinking ability had no significant relationship with Informatics learning outcomes (r = -0.049; Sig. = 0.697). Similarly, mathematical ability was not significantly related to Informatics learning outcomes (r = 0.100; Sig. = 0.423). Simultaneously, logical thinking ability and mathematical ability also showed no significant relationship with Informatics learning outcomes (Sig. = 0.677) with a coefficient of determination (R²) of 0.012. These findings indicate that both variables accounted for only 1.2% of the variance in Informatics learning outcomes, while the remaining 98.8% was influenced by other factors outside the scope of this study. Therefore, logical thinking ability and mathematical ability were not significantly associated with the Informatics learning outcomes of eleventh-grade students at SMA Amal Mulia Boarding School Pekanbaru.